The Influence of Majority Ownership, Profitability, Size of the Board of Directors, and Frequency of Board of Commissioners Meetings on Sustainability Report Disclosure - Rina Trisnawati; Safari Dwi Wardati; Eskasari Putri (Universitas Muhammadiyah Surakarta, 2022)
Purpose – This study aims to determine the effect of majority ownership, profitability, the size of the directors board, and frequency of board of commissioners meetings on sustainability report disclosure.Design/methodology/approach– The data were tested using multiple linear regression method. The population used are LQ45 companies listed in Indonesian Stock Exchange (IDX) during the years 2017-2020. This study uses purposive sampling method and obtained 80 LQ45 companies for four years of observation.Findings– The results of this study indicated that the size of the directors board has a significant effect on sustainability report disclosure. While majority ownership, profitability, and frequency of board of commissioners meetings have no effect on sustainability report disclosure.Research limitations/implications– The board of directors is the highest element of management that has responsibility for gaining legitimacy. Companies that have a low number of boards of directors will disclose a higher sustainability report. A small board of directors will result in the effectiveness of coordination, communication and control of the CEO and result in participation that has a positive impact on monitoring information disclosure.Practical implications – Companies are expected to pay attention to sustainability reports disclosure because more high demands from stakeholders for non-financial information of each company.Originality/value – This study uses the majority ownership variable where this variable is very rarely used and uses the LQ45 company because previous research has focused on each industrial sector.